2004
DOI: 10.1242/jcs.01246
|View full text |Cite
|
Sign up to set email alerts
|

Shiga toxin binding to globotriaosyl ceramide induces intracellular signals that mediate cytoskeleton remodeling in human renal carcinoma-derived cells

Abstract: Shiga toxin is a bacterial toxin consisting of A and B subunits. Generally, the essential cytotoxicity of the toxin is thought to be mediated by the A subunit, which possesses RNA cleavage activity and thus induces protein synthesis inhibition. We previously reported, however, that the binding of the Shiga toxin 1-B subunit to globotriaosyl ceramide, a functional receptor for Shiga toxin, induces intracellular signals in a manner that is dependent on glycolipid-enriched membrane domains, or lipid rafts. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 62 publications
4
71
0
Order By: Relevance
“…Several studies have shown that Stx, upon binding or entry into cells, is able to trigger signaling cascades (Katagiri et al, 1999;Ikeda et al, 2000;Mori et al, 2000;Cameron et al, 2003;Takenouchi et al, 2004). However, the main focus has been on Stx-induced apoptosis and signaling related to this late event.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that Stx, upon binding or entry into cells, is able to trigger signaling cascades (Katagiri et al, 1999;Ikeda et al, 2000;Mori et al, 2000;Cameron et al, 2003;Takenouchi et al, 2004). However, the main focus has been on Stx-induced apoptosis and signaling related to this late event.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to activating endocytosis, Shiga toxin may influence signaling important for later trafficking events. After Shiga toxin binds to the cell surface, there is an increase in MT assembly and the number of microfilaments (Takenouchi et al, 2004). STxB stimulates dynein-based motility that may facilitate its own transport to the juxtanuclear Golgi apparatus (Hehnly et al, 2006).…”
mentioning
confidence: 99%
“…These kinases do not seem to regulate the uptake of the toxin, but rather to be involved in the endosome-to-Golgi transport step (see below). Moreover, Stx has been shown to stimulate microtubule assembly in ACHN cells [38] and in Vero cells [39], and both microtubules and dynein were found to be required for transport of Stx to the Golgi [39]. Notably, it was shown that the Stx-induced activation of microtubuli assembly was not mediated via Syk, suggesting that multiple signaling pathways are induced by Stx.…”
Section: B B Bmentioning
confidence: 99%